Penerapan Media Pembelajaran Berbasis Video Terhadap Motivasi Belajar Materi Renang - Salsabila, Dea; Hartoto , Setiyo; Arief , Nur Ahmad (Universitas Hamzanwadi, 2025)
This study aims to determine the effect of implementing video-based learning media on students' learning motivation in swimming lessons. The background of this study is based on the low learning motivation of students due to the use of conventional methods that are uninteresting and unsuitable for the learning styles of 21st-century students. The research method used is a quasi-experimental design with a pretest-posttest control group. The population in this study consists of all eighth-grade students at SMP Negeri 3 Sidoarjo, totaling 224 students. The total sample size is 56 students. Data analysis techniques use SPSS. The instrument is in the form of a closed-ended questionnaire with a Likert scale. The results of the data analysis showed a significant increase in learning motivation in the experimental group compared to the control group. The average motivation score of the experimental group increased from 2.939 to 4.207, while the control group increased from 2.811 to 3.075. These findings reinforce that video-based learning media can deliver swimming material more effectively and enjoyably, while also building students' affective engagement. Thus, the use of educational videos is a relevant and innovative alternative strategy for enhancing students' learning motivation in physical education, particularly in swimming instruction.